Complexos de rênio(I) e cobalto(III) como candidatos a metalofármacos antitumorais - Camila Vargas Garcia (2017)
The present study involved the investigation of rhenium(I) and cobalt(M) complexes coitaining Schiff bases with antiproliferative activity for the development of new antitumor metallopharmaceuticals candidates. Rhenium(I) complexes have not been investigated extensively for their applications as cytotoxic agents. In the present work the complexes [ReCI(CO)3(H2AcPh)] (1), [ReCl(C0)3(H2AcpCIPh)].0.5C711,3 (2) and [ReCI(C0)3(H2AcpNO2Ph)].0.5C711.3 (3) were obtained with 2-acetylpyridine-phenyilaydrazone (12AcPh), 2-acetylpyridine-para-chlorophenylhydrazone (H2AcpC1Ph) and 2-acetylpyridine-para-nitrophenylhydrazone (H2AcpNO2Ph). Complexes (1-3) showed antiproliferative activity against NCI-H460 human lung carcinoma cells, with 3 showing the best result. Moreover, the complexes were more active than the free hydrazones. Complexes 1-3 also presented cytotoxicity against non-malignant HUVECs (human umbilical vein endothelial) cells, suggesting that they could also have antiangiogenic activity. 2 and 3 induced apoptosis with subsequent mitochondrial disruption on NCI-H460 cells and showed a dose-dependent high antioxidant activity (reduction on reactive oxygen species production). The complexes were not active against different species of Candida genus' fungi and Gram-positive and Gram-negative bacteria. These results are promising from the point of view of development of new antitumor metallopharmaceuticals making relevant the investigation of 186.1ssRe analog complexes as potential metalloradiopharmaceuticals. Caban(:II) complexes with antineoplastic ligands have been used as bioreductive pro-drugs to be selectively activated at hypoxia regions. Therefore, complexes [Co(2AcPh)21C12H20 (4), (Co(2AcpCIPh)21C1.3.5H20 (5) and [Co(2AcpNO2Ph)21C12.5H20 (6) were obtained with H2AcPh, H2AcpCIPh and H2AcpNO2Ph, as well as [Co(2Ac4Ph)21CI-C11.30H-0.5H20 (7), [Co(2Ac4pCIPh)2]C1-1.5H20 (8), [Co(2Ac4oCIPh)21C1-3.5H20 (9), [Co(2Ac4pNO2Ph)2]C1-3H20 (10) and ro(2Ac4oNO2Ph)2.1C1-3H20 (11) with 2- acetylpyridine-N(4)-phenylthiosemicarbazone (H2Ac4Ph), 2-acetylpyridine-N(4)-para-chlorophenykhiosemicarbazone (H2Ac4pC1Ph), 2-acetylpyridine-N(4)-orto-chlorophenyltbiosemicarbazone (H2Ac4oCIPh), 2-acetyliFidine-N(4)para-nitrophenylthioseinicarbazone (InAc4pNO2Ph) and 2-acetylpyridine-N(4)-orto-nitrophenylthiosenncarbazone (H2AoloNO2Ph). Electrochemical studies showed that cobalt(111) complexes with hydrazones (4-6) have a more favorable reduction potential than the analogs with thiosemicarbazones (7-11). The half-wave potential values (Ern-) obtained for complexes (4-6) are within the cellular reductants range. Furtheraore, it was observed that the Com/Co° reduction process happens by a quasi-reversible mechanism. Reduction studies, accompanied by electronic spectroscopy and mass spectrometry, showed that complex (4) was reduced in the presence of 3 mol equivalents of sodium dithionite (Na2S204) with subsequent H2AcPh ligand release. On the other hand, the reduction of the analogue complex with thiosemicarbazone (7) was not observed in the presence of 3 or 10 mol equivalents of Na2S204 in a 24-hours period. Considering that the cobalt(III) complexes have two ligands per cobalt atom, it was verified that, in general, the hydrazones and thiosemicarbazones showed to be more active than their complexes against HL60, Jurkat and THP-1 leukemia and MCF-7, MDA-MB-231 and HCT-116 solid tumor cells. The best results were observed for complexes (7) and (8) which proved to be considerably less active than the F2Ac4Ph and H2Ac4pCIPh ligands against the solid tumors cells. In addition, these compounds presented low cytotoxicity against Vero (green monkey kidney) non-malignant cells. However, no difference in the activity was observed for complexes (4-5 and 7-8) against MCF-7 cells when the cells were cultured in monolayer (2D) or in the three-dimensional soft-agar (3D) models. Although complexes (4-5) do not show selectivity against MCF-7 cells cultured in the 3D model, the cytotoxic properties and the electrochemical behavior of cobalt(M) complexes with hydrazones make them potentially suitable to be used as bioreductible pro-drugs. In this way, the investigation of the cytotoxic effects of these compounds against other solid tumor cell lines in hypoxia chamber is of utmost relevance. Considering the need to understand the other bioactivities of potential antineoplastics drug candidates, an evaluation of the antimicrobial effects of the cobalt(M) complexes under study was carried out. Overall the complexes with thiosemicarbazones showed higher activity against Gram-positive bacteria than those with hydrazones. The hydrazone complexes showed antifungal activity against Candida genus' fungi. Both rhenium(I) and cobalt(Ill) complexes were able to suppress humam serum albumin (HSA) fluorescence with formation of a 1:1 metal complex-HSA system. The interaction occurs by means of a static mechanism, suggesting that the complexes could be transported by this protein which has several physiological functions in the organism. Thus, coordination of rhenium(I) and cobalt(M) to cytotoxic Schiff base ligands, such as hydrazones and thiosemicarbazones, revealed to be an interesting strategy for the planning of new antitumor metallophannaceutical candidates. The present work constitutes an important contribution to Inorganic Medicinal Chemistry.